Network Culture as a Modus of Mass Culture in Contemporary Society - Пищик, Софія Владиславівна (Politology bulletin, 2024)
It has been proven that the rapid development of modern information and communication technologies, particularly visual media technologies, has drastically altered the cultural landscape of contemporary society. These technologies have created new opportunities for the exchange of information and cultural values, while simultaneously generating a range of socio-psychological problems. Contemporary society functions in an environment where visual images have become the primary means of communication. The influence of the so-called “visual turn” in culture, which began in the second half of the 20th century, continues to grow today. As a result, new forms of visual communication have emerged, becoming dominant in the media space, which necessitates a reconsideration of traditional approaches to cultural analysis.It is revealed that network technologies, such as social media, video platforms, and digital media, significantly affect people’s behavior, their perception of the world, and the formation of cultural values. Social platforms, particularly Instagram, YouTube, and TikTok, have become key tools for the creation and dissemination of visual content, which actively influences cultural practices and social processes. This leads to changes in how people interact with information, consume it, and form their perceptions of reality. Positive aspects of this process include access to a wide range of information and cultural products. However, alongside the positive outcomes, phenomena such as information overload and content fragmentation present new challenges for the comprehension and structuring of information.It has been found that contemporary culture, based on visual images, requires new forms of critical analysis, as visual media significantly alters the perception of reality and social norms. Images that are widely disseminated through media platforms are capable of shaping social stereotypes that influence both individual and collective identities. This demands the development of new approaches to studying visual culture and its impact on society. For instance, research shows that the fragmentation of visual forms and their constant renewal complicate the formation of a unified and coherent understanding of culture and social processes.

Доведено, що стрімкий розвиток новітніх інформаційно-комунікаційних технологій, зокрема візуальних медіатехнологій, кардинально змінив культурний ландшафт сучасного суспільства. Ці технології створили нові можливості для обміну інформацією та культурними цінностями, водночас породивши ряд соціально-психологічних проблем. Сучасне суспільство функціонує в середовищі, де візуальні образи стають основним засобом комунікації. Вплив так званого «візуального повороту» в культурі, який розпочався в другій половині XX століття, продовжує зростати й сьогодні. Завдяки цьому з’явилися нові форми візуальної комунікації, які стали домінуючими у медіапросторі, що вимагає переосмислення традиційних підходів до аналізу культури.Розкрито, що мережеві технології, такі як соціальні мережі, відеоплатформи і цифрові медіа, істотно впливають на поведінку людей, їхнє сприйняття світу та формування культурних цінностей. Соціальні платформи, зокрема Instagram, YouTube та TikTok, стали ключовими інструментами для створення та поширення візуального контенту, що активно впливає на культурні практики і соціальні процеси. Це викликає зміни в тому, як люди взаємодіють з інформацією, споживають її та формують свої уявлення про реальність.Позитивні аспекти цього процесу включають доступ до широкого спектру інформації та культурних продуктів. Однак, крім позитивних результатів, такі явища, як інформаційне перевантаження та фрагментація контенту, створюють нові виклики для осмислення та структуризації інформації.Виявлено, що сучасна культура, заснована на візуальних образах, потребує нових форм критичного аналізу, оскільки візуальні медіа суттєво змінюють сприйняття реальності та соціальних норм. Зображення, що активно поширюються через медіаплатформи, здатні формувати соціальні стереотипи, які впливають на індивідуальну та колективну ідентичність. Це вимагає розвитку нових підходів до дослідження візуальної культури та її впливу на суспільство. Наприклад, дослідження показують, що фрагментарність візуальних форм і їхнє постійне оновлення ускладнюють формування єдиного і цілісного уявлення про культуру та суспільні процеси.
Мережева культура як модус масової культури сучасного суспільства
Keywords: network culture; mass culture; visual media; social networks; cultural practices; identity; media literacy; information technologies; мережева культура; масова культура; візуальні медіа; соціальні мережі; культурні практики; ідентичність; медіаграмотність; інформаційні технології